The effect of chemical and physical imperfections in zircon grains in influencing the U-Pb age analyses: Insights from zircon fission track etching - Resende, Rosana Silveira [UNESP]; Tello Sáenz, Carlos Alberto [UNESP]; Pereira, Luiz Augusto Stuani [UNESP]; Dantas, Elton Luiz (Elsevier, 2019)
Understanding the chemical etching effects in the crystalline structure of zircon grains is crucial to know their chemical composition, morphology and isotopic geochemistry. After chemical etching, the zircon grain can be classified as homogeneous heterogeneous, hybrid and anomalous depending on the surface fission-track density observed under an optical microscope. The complementary techniques such as optical microscopy, micro-Raman spectroscopy, scanning electron microscopy (imaging by cathodoluminescence and secondary electrons) and electron microprobe, were employed to characterize the zircon grain surfaces from Igneous, Metamorphic and Sedimentary rocks before and after chemical etching, except for Raman spectroscopy. Measurements of U-Pb age are concordant in areas on the grain surface with uniform fission-track density. The chemical and isotopic analyses show that the etching is capable of revealing the different layer imperfections of the zircon crystalline structure, which can be inherent in its crystallization or acquired during its geological history. Therefore, identification of crystallographic preserved areas on the zircon surface, which are associated with uniform fission-track density, helps to get highly concordant U-Pb ages. In general, the results showed that the U-Pb system depends significantly on the amorphization degree of the zircon crystalline structure, which in most cases can only be revealed by etching.
Keywords: Crystalline structure; Etching; U-Pb system; Zircon fission track